Carbonstäbe im Bauwesen – Teil 3: Bestimmung der Zugtragfähigkeit. Issue 7 (1st June 2021) - May, Maximilian; Riegelmann, Philipp; Schumann, Alexander; Curbach, Manfred
Abstract: Nachdem im ersten Teil der Veröffentlichungsreihe die grundlegende Materialcharakteristik von Bewehrungsstäben aus Carbonfasern und im zweiten Teil deren Verbundtragverhalten zur umgebenden Betonmatrix beschrieben wurde, wird nun die Bestimmung der Zugtragfähigkeit von Carbonstäben für das Bauwesen thematisiert. Aufgrund der Querdruckempfindlichkeit der Carbonfasern ist der Lasteinleitungsbereich im Zugversuch der kritische Punkt und bedarf bei der Versuchsplanung besonderer Beachtung. Aufbauend auf dem Stand des Wissens zu Verankerungssystemen, die aktuell vor allem bei vorgespannten Bauteilen verwendet werden, wird die Entwicklung einer geeigneten Lasteinleitungskonstruktion vorgestellt, die eine zuverlässige Prüfung der Zugtragfähigkeit des untersuchten Carbonstabs ermöglicht. Abstract: Rebars made of carbon fibres for the use in civil engineering – Part 3 – Determination of the tensile strength After describing the basic material characteristics of carbon fiber reinforced rebars in the first part of the publication series and their composite load‐bearing behavior to the surrounding concrete matrix in the second part, the determination of the tensile load‐bearing capacity of carbon rebars for civil engineering is now discussed. Due to the transverse pressure sensitivity of carbon fibers, the load application area in the tensile test is the critical point and requires special attention in the test design. Based on the state of the art of anchorage systems, which are currently used mainly for prestressed components, the development of a suitable load introduction design is presented, which allows a reliable test of the tensile strength of the carbon rebars.